Considerations of post application in restoration of endodontically treated teeth: A review - M Ebrahimi Dastgerdi; A Khademi; K Khosravi; M Khoroushi; O Savabi; M Malekipour; P Hosseini Dastnaei (Isfahan University of Medical Sciences, 2010)
Using a post is a common method in providing the adequate retention for coronal restoration of endodontically treated teeth. With proper post selection, the success rate of this kind of treatment is considerable. In addition to post selection, some determining criteria including endodontic treatment, the remnant tooth structure, ferrule effect and some other factors should be considered. It is important to select a post with a proper length, diameter, type and material.Furthermore, modern brands of posts and contemporary cements have been introduced which assist dentists to present more variable treatment modalities. The endodontically treated teeth are very susceptible to fracture. Considering this fact that the occlusal forces partly transfer to the root through the post, an inappropriate post selection may enhance the tension on the post and on the root. The tensions can lead to three different situations: Loss of retention, post fracture and root fracture. Among these, the loss of retention is the most prevalent accident. However, root fracture would be probable if an improper post selected. Usually in this circumstance the final resort is tooth extraction.. Key words: Endodontically treated teeth, post, Coronal restoration, Retention.